2018
DOI: 10.1119/1.5055325
|View full text |Cite
|
Sign up to set email alerts
|

Towards Meaningful Physics Recognition: What does this recognition actually look like?

Abstract: In the February 2017 issue of The Physics Teacher, an article was presented that highlighted the importance of high school physics teachers in inspiring women in physics, particularly by recognizing them as being a “physics person.” Drawing on data from over 900 female undergraduates in physics, the article showed that the largest fraction became interested in physics careers during high school. In particular, being recognized by their physics teacher substantially increased the odds of their planning physics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 8 publications
2
36
0
Order By: Relevance
“…Educators in physics programs should focus on fostering female students' feelings of competency and recognize them for various capabilities and achievements, as well as create opportunities to prevent social alienation and isolation to improve sense of belonging. Prior work has found that creating communal classroom spaces can have a positive effect on female students' feelings of competence and recognition (Hazari & Cass, 2018). These communal spaces have students working together for everyone's benefit and resonate a cultural ethos that no one should be left behind.…”
Section: Discussionmentioning
confidence: 99%
“…Educators in physics programs should focus on fostering female students' feelings of competency and recognize them for various capabilities and achievements, as well as create opportunities to prevent social alienation and isolation to improve sense of belonging. Prior work has found that creating communal classroom spaces can have a positive effect on female students' feelings of competence and recognition (Hazari & Cass, 2018). These communal spaces have students working together for everyone's benefit and resonate a cultural ethos that no one should be left behind.…”
Section: Discussionmentioning
confidence: 99%
“…When planning OCSE activities, care must be taken to ensure that students, particularly women, are recognized as physics people. Based on the forms that recognition takes in high school classrooms [25], recognizing students in programmed OCSE activities translates to ensuring that activities are not only fun and engaging but also provide challenge. Students need to be provided with sufficient guiding support in these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the meanings of interest and performance/ competence are relatively straightforward, the meaning of being a physics person varies between individuals as do the actions that can cause individuals to perceive others as seeing them as a physics person [25]. According to a case study of high school physics classrooms, forms of recognition have been found to include setting high expectations and giving challenging assignments while at the same time providing students with the necessary support to meet those expectations and challenges [25]. Another form of recognition has been found to create a classroom environment that provides opportunities for students to take on leadership roles and demonstrate their expertise [10,25].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations